(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Within the context of the Saudi Arabian educational system, this research aims to investigate the significant impacts of participating in an online book club on dyslexic students’ reading engagement and reading pleasure. Reading comprehension and enthusiasm are two areas where people with dyslexia often struggle. A cross-sectional approach was used to look at 150 pupils who had been identified as having dyslexia. Half of the group was taking part in online literary conversations using the widely used website Goodreads to determine whether or not virtual book clubs are beneficial. Descriptive statistics, t-tests, and correlation analysis were used to determine how involved readers were and how much they enjoyed the text in this research. Research participants who participated in virtual book club activities reported higher levels of reading engagement and reading satisfaction compared to research participants who did not. One practical implication is the incorporation of online literary societies into existing educational programs, with the goal of creating welcoming environments for readers of all abilities.